Bale Ensiling Preserves Nutritional Composition and Phenolic Compounds of Red Grape Pomace - Gema Romero; Lidia Nieddu; Aymane Mouhssine; Paulina Nowicka; Joel Bueso-Ródenas; Nemesio Fernández; José Ramón Díaz (AgriEngineering, 2025)
Reusing agro-industrial by-products is a successful strategy that aligns with the 2030 Sustainable Development Goals. Red grape pomace poses a significant environmental challenge, particularly for wine-producing nations. Due to its high moisture content and seasonal availability, ensiling emerges as a potential method to prolong the nutritional value of red grape pomace, supporting the need for research into its application in animal nutrition. This study analyzed the bale ensiling process for red grape pomace by assessing its potential integration into ruminant diets and comparing its storage stability to untreated preservation methods. Baled silage units (approximately 300 kg each) were employed for this purpose. Analytical evaluations were conducted at 0, 7, 14, 35, 60, and 180 days of storage to monitor microbial and fermentation activity, nutritional composition, and bioactive attributes. Bale silage preserved the nutritional and microbial quality of red grape pomace for ruminant feed over a storage period of 180 days. The results demonstrated that bale silage successfully maintained the macro-composition, bioactive compounds, and antioxidant properties while reducing the fatty acid profile’s susceptibility to oxidation. By contrast, untreated storage led to significant spoilage. We concluded that bale ensiling is a suitable and effective technique that preserves red grapes for ruminant feed over a long period.